ETHNIC SEPARATISM: THEORETICAL BASIS OF CAUSES - Мосора, М. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The basic theoretical ideas to the causes of ethnic separatism presented in the article. The meaning of terms "separatism", "ethnic separatism" are ascertain. The modern state of theoretical concept ethnic separatism is research. The ethnic separatism, author accent, can manifest in any social formations, political regimes. The basic prerequisites and reasons tendency of separatism in ethnic group is analyze. The connection with ethnic separatism of national identity, socio-economic status, geographical location, religious and cultural differences, political and legal standards in the country is explained. Therefore, the importance of each of the catalysts reasons ethnic separatism is analized. Author point that the "politicization of ethnicity" antedate manifestations of separatism.